2019
DOI: 10.1371/journal.pbio.2006994
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated electrical activity in the olfactory bulb gates the oscillatory entrainment of entorhinal networks in neonatal mice

Abstract: Although the developmental principles of sensory and cognitive processing have been extensively investigated, their synergy has been largely neglected. During early life, most sensory systems are still largely immature. As a notable exception, the olfactory system is functional at birth, controlling mother–offspring interactions and neonatal survival. Here, we elucidate the structural and functional principles underlying the communication between olfactory bulb (OB) and lateral entorhinal cortex (LEC)—the gate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(91 citation statements)
references
References 96 publications
5
83
3
Order By: Relevance
“…The recorded network activity had a highly fragmented structure (defined as discontinuous activity) in all investigated areas (PFC, HP, LEC and OB). The full signal (i.e., entire LFP trace) consisted of transient episodes of oscillatory discharges with mixed frequencies (from here referred to as “active periods”), alternating with periods of relative electrical silence and suppressed activity (from here referred to as “silent periods”; Figure 1A; Khazipov et al, 2004; Hanganu et al, 2006; Brockmann et al, 2011; Bitzenhofer et al, 2017; Gretenkord et al, 2019). The prevalence of active periods decreased rapidly and robustly over time in all investigated brain areas upon urethane injection (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recorded network activity had a highly fragmented structure (defined as discontinuous activity) in all investigated areas (PFC, HP, LEC and OB). The full signal (i.e., entire LFP trace) consisted of transient episodes of oscillatory discharges with mixed frequencies (from here referred to as “active periods”), alternating with periods of relative electrical silence and suppressed activity (from here referred to as “silent periods”; Figure 1A; Khazipov et al, 2004; Hanganu et al, 2006; Brockmann et al, 2011; Bitzenhofer et al, 2017; Gretenkord et al, 2019). The prevalence of active periods decreased rapidly and robustly over time in all investigated brain areas upon urethane injection (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneous recordings of HP and PFC, as well as OB and LEC were analyzed to assess the effects of anesthesia on long-range functional coupling. We previously showed that at the end of the first postnatal week hippocampal theta bursts drive the oscillatory entrainment of local circuits in the PFC, whereas discontinuous activity in OB controls the network activity in LEC (Brockmann et al, 2011; Ahlbeck et al, 2018; Gretenkord et al, 2019). Urethane did not modify these interactions.…”
Section: Resultsmentioning
confidence: 99%
“…For testicular tissue clearing we adopted the CLARITY method ( Chung et al, 2013 ) with minor modifications ( Gretenkord et al, 2019 ). Briefly, testes from adult mice were fixed overnight at 4°C in hydrogel fixation solution containing 4% acrylamide, 0.05% bis-acrylamide, 0.25% VA-044 Initiator, 4% PFA in PBS -/- to maintain structural integrity.…”
Section: Methodsmentioning
confidence: 99%
“…While the precise definition of a 'brain state' can vary depending on the time scales of investigated phenomena, the link between ongoing (or spontaneous) brain activity and the current state of the brain is well accepted [8][9][10][11][12][13][14]. In fact, ongoing neural activity has been observed across the nervous system, from brain areas involved in sensory processing [15][16][17][18][19][20][21][22][23], to innate behaviors [24][25][26], and higher cognitive function [27][28][29][30][31][32][33][34][35][36][37]. Despite the presence of ongoing activity across the brain and its rapid alterations coupled with brain state transitions, dedicated neural pathways and their connection to ongoing brain activity and sensoryevoked transitions remain to be identified.…”
Section: Introductionmentioning
confidence: 99%